Paving the path to the future of carbogenic nanodots - Navneet C. Verma (Nature Portfolio, 2019)
Insufficient purification and incomplete characterization pose a serious problem for attributing photoluminescence properties to carbogenic nanodots, especially those synthesized by bottom-up approaches. Here, we provide a roadmap for the successful future of these nanodots.